Fuel cells : current technology challenges and future research needs - Behling, Noriko Hikosaka (Amsterdam : Elsevier, 2013)
'This book is a one of a kind, definitive reference source for technical students and researchers, government policymakers, and business leaders. It provides an overview of past and present initiatives to improve and commercialize fuel cell technologies. It provides context and analysis to help potential investors assess current fuel cell commercialization activities and future prospects. Most importantly, it gives top executive policymakers and company presidents with detailed policy recommendations as to what should be done to successfully commercialize fuel cell technologies.'--pub. desc.
Includes bibliographical references and index.
Keywords: Fuel cells